Paediatric serum sickness-like reaction: A 10-year retrospective cohort study. Issue 7 (3rd April 2021) - Del Pozzo-Magaña, Blanca R; Abuzgaia, Awatif; Murray, Barbara; Rieder, Michael J; Lazo-Langner, Alejandro
Abstract: Background: Serum sickness-like reaction (SSLR) is an acute inflammatory condition affecting predominantly children. The pathophysiology remains unclear, but drugs are considered the main trigger. Objective: The aim of this study was to describe the clinical and laboratory features, triggers, and treatment modalities in children diagnosed with SSLR. Methods: We conducted a 10-year retrospective cohort study including all paediatric patients (0 to 18 years old) with query SSLR referred to the Adverse Drug Reactions Clinic at the Children's Hospital of Western Ontario. Diagnostic criteria included acute skin rash plus joint inflammation with or without fever. Results: We included 83 patients (47 females). Age ranged from 11 months to 12 years (mean 3.2 years). Amoxicillin was the trigger in 82.7% of patients. The mean time between the exposure to the triggering drug and the development of the symptoms was 8.5 days. Urticaria-like and Erythema multiforme-like lesions were present in 35% and 38.5% of the cases, respectively. Joint inflammation affecting hands/feet was present in 60%. Pruritus, lip/eye swelling, and fever were reported in 33, 31, and 45% of patients, respectively. The lymphocyte toxicity assay (LTA) showed incremental T-cell toxicity in 32 of 34 patients. Children that received treatment with antihistamines/nonsteroidal anti-inflammatory drugs (NSAIDs) plus oral steroids had a mean recovery time shorter than those treated only with antihistamines/NSAIDs (6 versus 8 days; P=0.09). Conclusions: In our study, SSLR was mostly triggered by amoxicillin and had a mean time presentation of 8.5 days. Further prospective and well-conducted studies are needed. Graphical Abstract: